Change Management Strategies for Enhancing Education Quality at Islamic Boarding School - Abdurrahman Abdurrahman; Baharuddin Baharuddin; M Samsul Hady (AL-ISHLAH: Jurnal Pendidikan, 2025)
Islamic boarding schools (pesantren) have long been integral to the development of Islamic education in Indonesia, shaping both the educational landscape and cultural values. Pesantren are indigenous institutions with distinct advantages and a legacy of scientific and moral transmission. In the face of globalization and societal demands, these institutions continuously adapt to maintain their relevance and excellence. This qualitative field research employed a case study design to investigate the change management strategies in Islamic boarding schools aimed at enhancing educational quality. Data collection techniques included observation, interviews, and documentation, using snowball sampling to identify participants. Data were analyzed through reduction, presentation, and conclusion drawing, with validity ensured via triangulation, extended researcher participation, and persistent observation. Findings reveal that the change management process is spearheaded by the Kiai, who plays a collegial role involving all stakeholders. Change is implemented through the cultivation of both spiritual and social values, fostering collaborative efforts among educators, students, and community members. Stakeholder involvement is critical in designing and executing programs focused on improving the educational quality and competitiveness of pesantren. The success of change management in pesantren underscores the importance of inclusive leadership and value-driven reforms. By aligning traditional values with modern educational demands, Islamic boarding schools can sustain their pivotal role in Indonesia’s educational system while achieving excellence across various scientific disciplines.